Confusion Regarding the DASH Diet and Sodium Restriction in Inner-city Clinic Patients: Association with Poor DASH Scores and Sodium Adherence (P04-111-19) - Lembrikova, Katerina (Curr Dev Nutr, 2019)
OBJECTIVES: Adherence to the DASH (Dietary Approaches to Stop Hypertension) diet is associated with slower progression of kidney disease and decreased cardiovascular risk. We evaluated the association between knowledge of the DASH diet, DASH scores and nutrient intake in an inner-City population. METHODS: A random sample of patients from CKD (37), medicine/diabetes (18) and transplant clinic (31) was studied using 24-hour food recall, with nutrient intake analyzed by ASA24 software used to calculate DASH score. Patients were asked to respond to the question “Do you know what the DASH diet is?” RESULTS: Mean age was 63.8 ± 14.1yrs; 50% (43) had diabetes; 85% (73) had hypertension. 45% (39) reported income < $20 K/yr. 78% (67) stated that they were familiar with the DASH diet and defined it as decreased or “low” intake of sodium or salt (LoNa); 33% (28) were not familiar (NoAns). No patient was able to provide a correct explanation of the DASH diet as per the U.S. Department of Health and Human Services. Most common answers were “no salt” (26), “low salt” (38), 3 pts described the limit of sodium as 2gm (2) or <80 mg (1). Several patients commented “nasty” or “tasteless”. Mean DASH scores were poor and did not differ between the two groups (LoNa 3.75 ± 0.88 vs NoAns 3.8 ± 0.8, P = NS), nor did intake of sodium (LoNa 2.51 ±0.96 g vs NoAns 2.59 ± 1.3 g, P = NS). There was no difference in creatinine (LoNa 2.0 ± 1.6 vs 1.79 ± 1.3 mg/dl, P = NS), BMI, blood pressure systolic or diastolic, income, education or marital status between the two groups. 92% (57/62) pts in the LoNa group answered yes to the question “Are you familiar with a low sodium diet” vs 1% (1/16) in the NoAns group, P < 0.0001. CONCLUSIONS: In our population of inner-City pts: 1. Understanding of the DASH diet was poor and equated with low or absent sodium intake with unclear understanding of actual amount. 2. DASH adherence was poor in all groups. 3. There was no difference in sodium intake between pts who stated that they knew about the DASH diet and those who did not. Neither group met the recommendations for < 2gm/d intake. 4. Pts who answered they knew what a DASH diet was were more likely to report familiarity with low sodium diets. 5. Confusion regarding the DASH diet and sodium restriction is common. As the DASH eating pattern is a more comprehensive change in dietary habits, targeted education may be needed in this population to improve overall adherence. FUNDING SOURCES: none.